Frutos de Schinus terebinthifolius Raddi: extração ativa, estudo fitoquímico e incorporação em filmes bioativos de pectina - Santos, Calila Teixeira (2017)
The present study had as main objective to obtain bioactive extracts of the fruits of Schinus terebinthifolius Raddi (STF), with antioxidant and antimicrobial action, for incorporation in a bioactive package for foods, besides inhibition of acetylcholinesterase. The extraction process performed by focussed microwave (EAMF) and ultrasound (UAE). The comparison between extraction methods was monitored by the biological activities of these extracts. The results showed that for the yield there was no significant difference. For the EAMF assays, the best value of phenolic (5950 ± 1.4 mgGAE / g) and total flavonoids (1750 ± 3.2 mgEQ / g) was at the extraction time of 25 minutes at 51 ° C and with 75% ethanol. For the assays obtained by EAU, the best total phenolic content was (92.2 ± 0.8 mgGAE / g) in the EAU 10 test (extraction time of 30 minutes at 42 ° C and 50% ethanol) And flavonoids (67.72 ± 1.0 mgEQ / g) in the UAE 12 assay (extraction time of 17.5 minutes at 60 ° C and 50% ethanol). The best values for percent inhibition (% SRL) were 87.3% (EAMF 8) and 31.3% (UAE 12). Mass spectrometry analysis showed the presence of phenolic compounds and terpenes. In relation to the antimicrobial activity of extracts obtained by EAMF, the MIC for S. aureus was 0.5 mg / ml for E. coli 0.25 mg / ml, whereas the extract of EAU presented MIC of 0.5 mg / Ml for the two microorganisms analyzed. In the phytochemical study, it was possible to isolate 7 substances: agasthiflavone, tetrahydrorobustaflavone, masticadienoic acid (Z), masticadienoic acid (E), schinol, gallic acid and squalene, as well as a mixture with unsaturated fatty acid profile and a mixture with trisaccharide characteristics. Their chemical structures being determined by spectrophotometric methods such as 1H and 13C NMR, UV and MS. Two of the 17 EAMF extracts were selected, which were incorporated into an active high-methoxylation pectin-based film called "Extract 2" and "Extract 8" in various concentrations (0, 1, 3 and 5%). The films had a mean thickness of 0.007 mm for all concentrations of the extracts tested. It was observed in relation to the mechanical properties that there was an interaction of the polyphenolic components of the extracts with the materials used in the production of the films. The films were more permeable to water vapor (6.18-7.80 g.mm/m2.h.kPa) than the control film (5.12 g.mm/m2.h.kPa). The films of both extracts showed good thermal stability independent of the concentration tested. The films produced in this study presented antioxidant activity, and the films added from extract 8 presented the best% SRL values (54.45 and 67.08, respectively). All films obtained inhibition halo against the microorganisms tested. In view of the results, it can be inferred that FTS have antioxidant potential, antimicrobial activity and high inhibition of acetylcholinesterase and can be used in cosmetics, nutraceuticals and food industry, as well as a promising alternative in the production of active films.